(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
In Medieval India, Bhakti and Sufi movement has created a paradigm shift for the socio-religious and cultural outlook of the common man’s life. The imagery and portrayal of the Almighty evolved from the Awful Omnipotent to Merciful Creator. The Orthodox religious system in both Hinduism and Islam were losing its popularity to the common mass. In order to overcome the ritualistic and rigid approach which is difficult to understand by the common people Bhakti and Sufi movement took place. The approach was simpler in performance and easy to understand to the common people. It was taught that instead of the rituals God is pleased with love of the worshipper. Rituals took a side place and mere reverence became loving reverence (Bhakti). This evolution occurred not only in Socio-religious aspect but also in literary aspect as well, because regional languages were used to write and teach the Bhakti tradition instead of the traditional Sanskrit and Classical Arabic. Regional language now used to teach the religious philosophy and poetries and songs replaced the hymns to worship the Almighty. In medieval Bengal, Bhakti tradition was popularized with Shri Chaitanya Deva in Gaudiya Vaishnavism theory. Parallelly Sufi tradition in North India was gradually popularizing. These traditions were also known as medieval mysticism. In colonial Bengal, Post Chaitanya Bhakti tradition was further evolved with Sufi and Tantric influence. Then a neo-religious Bhakti sect named Baul was generated. This Baul tradition and the practitioners of this tradition was outcasted from the society for their unorthodox practices. Among the Bengal Baul, Lalan Fakir is the most popular name. Lalan Fakir or Lalan Sain’s philosophy was reflected in his songs. In this article, my aim is to analyze the reflection of bhakti in form of Vatsalya in some of Lalan Fakir’s writing. In the conclusion, I would refer to the influence of Gaudiya Vaishnavism as found in Bengal Baul songs.